전 지구 관측망을 이용한 GPS 위성 시계 오프셋 실시간 추정 및 GPS 위성 블록에 따른 오프셋 특성 분석 - 설윤환; 림형진; 김영국; 박관동; Yunhwan Seol; Hyung-Jin Rim; Yeong-Guk Kim; Kwan-Dong Park (Journal of Positioning, Navigation, and Timing, 2025)
Centimeter-level precise positioning based on satellite navigation requires satellite clock offset accuracy at the nanosecond level, which is more precise than the time information provided by broadcast ephemeris. The development of precise real-time clock error estimation technology is therefore essential. This study developed a real-time Global Positioning System (GPS) satellite clock offset estimation algorithm based on a sequential filter. The algorithm estimates satellite clock offsets using data acquired from a global network of stations. The algorithm estimates the satellite clock offset, drift, receiver clock error, tropospheric zenith delay correction, and ambiguity parameters as state variables. The observation model uses un-differenced observations with an ionosphere-free combination technique. To improve the numerical stability of the Kalman filter, Cholesky decomposition and the Joseph stabilized form of the covariance update method were introduced. For validation, the results were compared with the final clock offset product from the Jet Propulsion Laboratory (JPL). The root mean square error (RMSE) was found to be 1.47 ns when using only carrier phase and 1.56 ns when using a combination of carrier phase and code. Additionally, a bias was observed depending on the GPS satellite block, with a magnitude reaching up to 2.5 ns.